ANALISIS POTENSI PENGEMBANGAN LAJUR SEPEDA TERINTEGRASI BRT DI DAERAH PERBUKITAN GUNUNGPATI KOTA SEMARANG - Suseno, Dhony Priyo; Kurniawan, Achmad; Utomo, Danang Setyo (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
The bike lane in Semarang city has the potential to be developed even though the topography is contoured by hills that divide the city into lower Semarang and upper Semarang. This study aims to determine the potential location of the bike lane development so that the bike mode in lower Semarang can be integrated with the Trans Semarang BRT to upper Semarang, or vice versa, especially to the Semarang State University (UNNES) campus area in Gunungpati district. The BRT integrated bike mode is expected to be able to make the city of Semarang a "Bicycle Friendly City". This research method uses a quantitative descriptive method with a BLOS (Bicycle Level Of Service) method approach. Primary data were obtained by interview techniques, field observations, field trip, and documentation. Secondary data were obtained through literature studies related to bike lane policies and standards. The results of this study are that the BLOS score in the UNNES area is 2.4 ”“ 2.88 (ranks B and C) with a good environmental description and good enough for bicycles. The conclusion is the development of bike lanes and facilities can be applied in the campus area with limited integration of Trans Semarang BRT, related to type and amount of bike, integrated and transit halte locations that support Bike on Board facilities. The Most implication of this research results is that it can increase the participation of students as agents of the younger generation who have an influence in a change.